From Policy to Practice: The Roles of Philippine Government Agencies in Work-Related Compensation Claims of Filipino Seafarers - Jhundel Ricamonte Ropa (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Filipino seafarers play a vital role in the maritime industry; however, many still face challenges in accessing timely and equitable compensation for work-related illness, injury, or death incurred during employment. This study examined the roles of Philippine government agencies in addressing compensation claims, the procedural mechanisms they employ, and the reforms needed to strengthen the process under Republic Act No. 12021, the Magna Carta of Filipino Seafarers. This study employed an exploratory qualitative research design using a phenomenological approach. Data were gathered through in-depth interviews with 10 Filipino seafarers, two beneficiaries, and five key informants from the Department of Migrant Workers (DMW), Overseas Workers Welfare Administration (OWWA), Department of Labor and Employment/National Conciliation and Mediation Board (DOLE/NCMB), Maritime Industry Authority (MARINA), and Public Attorney’s Office (PAO). Relevant laws, policies, and agency procedures were also reviewed. Data were analyzed using Braun and Clarke’s (2006) thematic analysis framework. Findings revealed that while government agencies provide legal, welfare, administrative, regulatory, and dispute resolution support, the compensation claims system remains fragmented, procedurally complex, and burdensome for claimants. Implementation gaps persist despite RA 12021, highlighting the need for stronger inter-agency coordination, digitalized claims processing, enhanced legal and medical support, and improved information dissemination. The study concludes that while the government has established institutional mechanisms to protect seafarers’ compensation rights, translating policy into claimant-centered practice requires significant reforms. These reforms are necessary to achieve a more accessible, transparent, and equitable compensation claims framework for Filipino seafarers.